Peluang dan Tantangan UMKM Kelurahan Kebonsari Pasca Pandemi 2022 - Aldila Putri Selsha Kirani; Puteri Rafika Nur Alya; Reninta Mayang Sari; Kinanti Resmi Hayati (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
The economic aspect, especially for Micro, Small, and Medium Enterprises (MSMEs) is greatly affected due to this pandemic. The current rules are not fully known to the public, so they do not understand what the opportunities and challenges are in this new standard era because they are still not 100% free from corona, that's why we made this research. The subjects of this research are Micro, Small, and Medium Enterprises (MSMEs) in Kebonsari Village, Surabaya, the length of the study was carried out from March to early June 2022. The research conducted was survey research and data analysis. directly and the use of questionnaires. The government's latest policy has caused changes in people's behavior which is usually called the new standard era, almost all community activities are carried out online. MSME actors must pay attention to product quality, by paying attention to and improving product quality, the level of consumer satisfaction will increase. Therefore, MSME actors must be able to pay attention to the opportunities and challenges that exist